2003
DOI: 10.1021/ol0349662
|View full text |Cite
|
Sign up to set email alerts
|

Second-Chance Rearrangement Route to Novel 5(6)-Syn,anti-difunctional 2-Azabicyclo[2.1.1]hexanes

Abstract: [reaction: see text] The first syntheses of 5,6-difunctionalized-2-azabicyclo[2.1.1]hexanes containing syn-hydroxy and syn-fluoro substituents have been effected in a stereocontrolled manner. The key reactions are regioselective additions to the aziridinium ions formed from 6-exo-iodo(bromo)-5-endo-X-2-azabicyclo[2.2.0]hexanes (X = F, OH) upon silver or mercury salt enhancement of iodide nucleofugacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 16 publications
0
23
0
Order By: Relevance
“…12 Conversion of fluoroalcohol 18 to the thionocarbonate 19 using phenylchlorothionocarbonate 13 followed by reductive deoxygenation afforded the N -benzyloxycarbonyl fluoride 20 . Reductive removal of the protecting group using H 2 /Pd(OH) 2 in methanol in the presence of (BOC) 2 O afforded the N -BOC-5- syn -fluoro synthon 10a .…”
Section: Resultsmentioning
confidence: 99%
“…12 Conversion of fluoroalcohol 18 to the thionocarbonate 19 using phenylchlorothionocarbonate 13 followed by reductive deoxygenation afforded the N -benzyloxycarbonyl fluoride 20 . Reductive removal of the protecting group using H 2 /Pd(OH) 2 in methanol in the presence of (BOC) 2 O afforded the N -BOC-5- syn -fluoro synthon 10a .…”
Section: Resultsmentioning
confidence: 99%
“…15 Further studies revealed that the participation of both s and p electrons played an important role in controlling the stereochemistry of such rearrangements. 21 For such compounds, the silver-promoted rearrangement of each stereoisomer at the nitrogen atom (invertomers) proved to be dependent on the configuration at nitrogen.…”
Section: Ring Rearrangementsmentioning
confidence: 99%
“… N- Boc- and N- Cbz derivatives of the parent 2-azabicyclo[2.1.1]hexane derivatives have been described. 3a, …”
Section: Referencesmentioning
confidence: 99%
“…There has been substantial recent interest in the 2-azabicyclo[2.1.1]hexane ring system, which forms the basis for the nonproteinogenic amino acid 2,4-methanoproline . Early synthetic routes to the ring system were based on photochemical intramolecular [2 + 2] cycloaddition strategies, and there have been recent reports of alternative approaches, from 2-azabicyclo[2.2.0]hexane derivatives, 3-halomethyl-1-aminocyclobutanes, , and cis- cyclobutene dicarboxylic anhydrides so that the azabicyclic framework itself is now readily available.
…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation